LEGAL FOUNDATIONS OF LOCAL SELF-GOVERNMENT IN RUSSIA - Kuchenin, Evgeny; Nikodimov, Igor; Loshkarev, Igor; Tchinaryan, Elena (Revista Inclusiones, 2019)
The article is devoted to the study of the structure and functions of local self-government in the Russian Federation. Both general and special scientific methods of cognition have been used. The general scientific methods include induction, deduction and system analysis. Statistical, analytical, formal-legal and system-structural methods are applied as well. The constitutional and legal essence of local self-government and its position in the system of bodies possessing authority are revealed. The purpose of this article is to study the legal foundations of local self-government in the Russian Federation. As a result, it is concluded that local self-government and state power are forms of public power that exist in the Russian state. The legislative regulation of local selfgovernment at the federal and regional levels through normative legal acts and in the statutes of municipalities at the local level is established. The structure of local self-government isdescribed, which includes the possibility of the formation of other bodies and officials of local government. The main functions of local self-government are revealed. The existing models of local government organizationare established, including the traditional model of local government, "elected mayor and strong manager", "city-manager", "council-commission" and "leader-cabinet".